Global Existence and Uniqueness of Strong Solutions for the Magnetohydrodynamic Equations. (27th November 2007) - Zhang, Jianwen
Abstract : This paper is concerned with an initial boundary value problem in one-dimensional magnetohydrodynamics. We prove the global existence, uniqueness, and stability of strong solutions for the planar magnetohydrodynamic equations for isentropic compressible fluids in the case that vacuum can be allowed initially.